Formation of Students’ Intercultural Competency on the Basis of the Textocentric Approach - N. N. Klementsova (Высшее образование в России)
The task of training a highly cultured person within the framework of university education involves mastering the intercultural (universal) competency necessary for efficient communication and self-development throughout life. The article aims at finding out the possibilities of the textocentric approach in the development and use of the technology for forming the intercultural competency of a non-linguistic university student.The concept substantiating the suggested technology is based on the idea of using the developing potential of the textual activity, the latter dominating language classes in a non-linguistic university. The established correlation of textual skills, indicating a number of activities fundamental for self-realization of the students, with the components of their intercultural competency indicates the possibility of using textual activity in forming intercultural competency, determining its structural components and substantiating a component-by-component assessment in order to identify the level of its formation.The experimental testing embracing 460 students of Kaliningrad State Technical University involved the use of the technology algorithm providing for logically structured textual activity in foreign language classes, as well as training and methodological support of the technology provided by the university.Diagnostics of the competency formation level was carried out using the author’s method of express and detailed diagnostics. As a result of experimental work, the formation level of intercultural competency of students upon entering the university was defined as conditionally basic; social and communicative components of the intercultural competency were specified as the least developed ones; the pedagogical conditions for the efficient implementation of the technology were determined and created. The detailed diagnostics revealed significant dynamics in the level and component development of the intercultural competency of the students in the experimental groups compared with the results of the groups conventionally considered as the control ones. The greatest difference among the indicators of the formation of the competency components concerned the social (42%) and informational (34%) components. At the end of the language course 70.7% of the students of the experimental groups were at a productive level of intercultural competency development.Experimental work confirmed the efficiency of the technology for the formation of intercultural competency based on the textocentric approach and determined the conditions for its use in a nonlinguistic university.